Maslov indices for lagrangian triplets - Karabatman, Ferhat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
In this thesis, we study the properties and an application of Maslov ternary index. By nding some special elements which generate symplectic group, we show that Maslov ternary index becomes a very important tool in the process of calculating the signature of a Lefschetz bration. Besides, we will provide easier proofs of some known theorems by using those special elements.
Keywords: Maslov index; Mathematics.